2018
DOI: 10.3390/land7010032
|View full text |Cite
|
Sign up to set email alerts
|

Forest Cover Change, Key Drivers and Community Perception in Wujig Mahgo Waren Forest of Northern Ethiopia

Abstract: This study assessed forest cover change from 1985 to 2016, analyzed community perception on forest cover change and its drivers, and suggested possible solutions in northern Ethiopia. Landsat images of 1985, 2000 and 2016, household interviews and focus group discussions were used. While dense forests and open forests increased by 8.2% and 32.3% respectively between 1985 and 2000, they decreased by 10.4% and 9.8% respectively from 2000 to 2016. Grasslands and cultivated land decreased in the first period by 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…A major increase was observed in semi-open forest and bush, which increased from 10.54 to 34.7%. These results correspond to the findings of Kukkonen and Kayhko (2014) in Unguja Island and Solomon et al (2018) in Wujig Mahgo Waren, Northern Ethiopia This study has also revealed that since 1975, a large part of the forest has been transformed to shrub forest and semi-open forest and bush (Table 5 and Figure 2). Only about 4129.9 ha had remained as forest in 2014.…”
Section: Patterns Of Land Cover Changes From 1975 To 2014supporting
confidence: 88%
See 1 more Smart Citation
“…A major increase was observed in semi-open forest and bush, which increased from 10.54 to 34.7%. These results correspond to the findings of Kukkonen and Kayhko (2014) in Unguja Island and Solomon et al (2018) in Wujig Mahgo Waren, Northern Ethiopia This study has also revealed that since 1975, a large part of the forest has been transformed to shrub forest and semi-open forest and bush (Table 5 and Figure 2). Only about 4129.9 ha had remained as forest in 2014.…”
Section: Patterns Of Land Cover Changes From 1975 To 2014supporting
confidence: 88%
“…The major concern on land cover change has emerged following the massive removal of the natural vegetation by human activities (Kull, 2012;Misana et al, 2012). The intensity of changes has been propelled by direct and indirect causes arising from human decisions at global to local levels (Solomon et al, 2018;Mwangi et al, 2017b;Adedeji et al, 2015). The decisions determine the human actions to control and access natural resources, leading to clearing of natural vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect drivers are population growth, essential for commodities, governance, and economic growth. [4][5][6][7] LULC change is also a major challenge with a strong impact on the agricultural development process and the implementation of the country's main development strategies, such as the growth and transformation plan developed by Ministry of Finance and Economic Development and the 2011 climate-resilient green economy strategy. 8 Remote sensing provides complete, area-wide observations of LULC at a variety of temporal and spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…The LULC maps are used in a variety of application areas. These include watershed management (40), hydrology (31), lowland management (21), highland management (20), urban studies (12), social studies (12), forest management (6) and agriculture (4). This implies that authors find the LULC analysis quite important for water-related applications such as watershed management or surface and groundwater hydrology in Ethiopian river basins like the Upper Blue Nile, Tekeze, Awash, Baro, Ghibe and Rift Valley Lakes basins.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Fuel wood collection, timber extraction, commercial agriculture and charcoal production are the primary direct drivers. Indirect drivers are population growth, essential for commodities, governance and economic growth [4][5][6][7]. LULC change is also a major challenge with a strong impact on the agricultural development process and the implementation of the country's main development strategies, such as the Growth and Transformation Plan (GTP) developed by Ministry of Finance and Economic Development (MoFED) and the 2011 Climate Resilient Green Economy strategy (CRGE) [8].…”
Section: Introductionmentioning
confidence: 99%